Social Media Activism: Water as a Common Good - Cernison, Matteo (Protest and Social Movements, 2018)
This book focuses on the referendums against water privatisation in Italy and explores how activists took to social media, ultimately convincing twenty-seven million citizens to vote. Investigating the relationship between social movements and internet-related activism during complex campaigns, this book examines how a technological evolution-the increased relevance of social media platforms-affected in very different ways organisations with divergent characteristics, promoting at the same time decentralised communication practices, and new ways of coordinating dispersed communities of people.Matteo Cernison combines and adapts a wide set of methods, from social network analysis to digital ethnography, in order to explore in detail how digital activism and face-to-face initiatives interact and overlap. He argues that the geographical scale of actions, the role played by external media professionals, and the activists' perceptions of digital technologies are key elements that contribute in a significant way to shape the very different communication practices often described as online activism.